Caracterizacion morfologica de hongos fitopatógenos en el cultivo de tomate horticola (solanum lycopersicum) sector Patain Cotopaxi 2014 - Chicaiza Paltán, Ana Lucia (2014)
2014”, It aimed to morphologically characterize the fungus that causes the greatest impact on production of horticultural tomato crop (Solanum lycopersicum) in “Patain” sector, Salcedo Canton, Cotopaxi province. The research was conducted by laboratory isolation techniques and the subsequent observation of the fungus in the microscope to differentiate their parts and then ratify the existing literature. Among the fundamental aspects of this research they are: The determination of the phytophatogenic fungus with greater impact on horticultural tomato production happened to be Phytophthora infestans, which was determined by the review and discussion of the literature, managing to identify the signs and symptoms of the fungus in field. The used technique was direct observation compared with the cited source, allowing us to perform the characterization of macro and micro structures such as: talo….